2008
DOI: 10.1002/pat.1218
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical applications of imidazolium cation‐modified iron oxide nanoparticles

Abstract: We report the synthesis of N‐methylimidazolium chloride‐modified iron oxide nanoparticles (MImCl‐NPs) by condensation of an imidazolium cation‐containing silane coupling agent (1) with the iron oxide nanoparticles which were prepared by the coprecipitation of FeCl2 and FeCl3 by alkaline hydrolysis. The modified iron oxide nanoparticles exhibited a superparamagnetic behavior at the room temperature. For a given weight concentration, MImCl‐NPs showed a darker (T2‐weighted) image than Resovist®, which is commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…The magnetization curve of the MNPs (black) and M@PEI nanoparticles (blue) were measured at room temperature, and the magnetization was normalized by the mass of all of the particles, as shown in Figure . The MNPs had a high magnetic value of 52.4 emu/g . After decoration by PEI, the magnetic value was 31.2 emu/g before it decreased; this indicated that the increase in the shell thickness caused a reduction in the magnetic value to a certain extent .…”
Section: Resultsmentioning
confidence: 94%
“…The magnetization curve of the MNPs (black) and M@PEI nanoparticles (blue) were measured at room temperature, and the magnetization was normalized by the mass of all of the particles, as shown in Figure . The MNPs had a high magnetic value of 52.4 emu/g . After decoration by PEI, the magnetic value was 31.2 emu/g before it decreased; this indicated that the increase in the shell thickness caused a reduction in the magnetic value to a certain extent .…”
Section: Resultsmentioning
confidence: 94%
“…To form a water-dispersive aggregate of gold nanoparticles, the carboxylate anion 1, which has a photo-cleavable functional group, was mixed into the imidazolium-presenting gold nanoparticles by employing ionic liquid structures 33,34 via anion exchange with chloride anions. Under aqueous conditions, the gold nanoparticles should be aggregated because of the enhanced hydrophobicity due to 1.…”
Section: Resultsmentioning
confidence: 99%
“…surface modification of metal nanoparticles involving. [8] Next, key materials have been required to extend the validity of SPIO-based probes for imaging and sensing.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…[8] By the surface exchange to tributylhexadecylphosphonium bromide under sonication with the oleic acidcoated SPIO 1, the desired product was prepared. NP2 was also obtained via the surface exchange with the silica-coated SPIO 2.…”
Section: Composite Interfaces 561mentioning
confidence: 99%
See 1 more Smart Citation